Biosci. J. 2016
DOI: 10.14393/bj-v32n1a2016-33014
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous glutathione reduces the damage induced by cadmium in cucumber seedlings

Abstract: Cadmium (Cd) toxicity is a worldwide problem for crop production. The present work used hydroponic experiments to investigate the ameliorating effects and physiological mechanisms of glutathione (GSH) mitigation of Cd toxicity in cucumber seedlings. The results revealed that Cd was mainly accumulated in roots of cucumber, 100 µM GSH pretreatment in 50 µM Cd solution significantly recovered Cd-induced growth inhibition, improved photosynthetic and chlorophyll fluorescence performance. Moreover, external GSH obv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(35 reference statements)
1
0
0
Order By: Relevance
“…Furthermore, C i increased markedly after Cd stress; at the same time, Cd + GB suppressed Cd-induced increase; therefore, no stomatal limitation and decrease of SPAD value contributed to the inhibition of photosynthetic processes in Cd-stressed cucumber seedlings. This result was consistent with our previous results (Sun et al 2016b). The present results showed that exogenous GB might positively affect photosynthesis and promote cucumber seedling growth under Cd toxicity.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, C i increased markedly after Cd stress; at the same time, Cd + GB suppressed Cd-induced increase; therefore, no stomatal limitation and decrease of SPAD value contributed to the inhibition of photosynthetic processes in Cd-stressed cucumber seedlings. This result was consistent with our previous results (Sun et al 2016b). The present results showed that exogenous GB might positively affect photosynthesis and promote cucumber seedling growth under Cd toxicity.…”
Section: Discussionsupporting
confidence: 94%